Analysis of CdS/CdTe thin film solar cells as a function of CdS doping concentration: a numerical simulation perspective - Hor, Chan Git; Badariah Bais,; Kazi Sajedur Rahman,; Puvaneswaran Chelvanathan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Cadmium Telluride (CdTe) photovoltaics, incorporating a thin film of Cadmium Sulfide (CdS), present a cost-effective yet less efficient solar cell technology. Improving CdS/CdTe solar cell efficiency involves optimizing parameters like doping concentration and CdS layer thickness. However, limited research on cell defects necessitates a comprehensive analysis, including the often-overlooked impact of temperature. This study aims to analyze defect-free and defective CdS/CdTe solar cells, exploring the effects of doping concentration and other parameters. Using the SCAPS-1D simulator, design parameter variations will be investigated, and key metrics—open-circuit voltage (Voc), short-circuit current density (Jsc), fill factor (FF), and efficiency (η)—will be extracted. Simulation results indicate minimal efficiency impact from increased doping concentration in the n-type CdS layer for defect-free devices. The optimal doping concentration for CdS is 5 × 1018 cm-3, with an optimum electron affinity of 4.0 eV. CdS thickness shows no significant efficiency impact, with the chosen optimum at 10 nm. In the defect-free CdS/CdTe solar cell, key metrics were Voc: 1.06 V, Jsc: 24.60 mA cm-2, FF: 87.89%, and η: 23.01%. Analysis of defects revealed single acceptor defects significantly impacting solar cell performance in both interfacial and bulk defects. Defect structure simulations demonstrated that increasing doping concentration, decreasing electron affinity, and thickness enhance efficiency. New optimum values for these parameters—1 × 1018 cm-3, 4.0 eV, and 10 nm—yielded Voc: 1.03 V, Jsc: 23.88 mA cm-2, FF: 87.15%, and η: 21.40%. Additionally, a temperature decrease was associated with increased efficiency.